Feasibility and safety of left atrial access for ablation of atrial fibrillation in patients with persistent left superior vena cava. Issue 3 (29th January 2022) - Kantenwein, Verena; Telishevska, Marta; Bourier, Felix; Kottmaier, Marc; Brkic, Amir; Risse, Elena; Popa, Miruna; Lengauer, Sarah; Kolb, Christof; Deisenhofer, Isabel; Hessling, Gabriele; Reents, Tilko
Abstract: Background: In patients with persistent left superior vena cava (PLSVC) ablation procedures can be challenging. We sought to determine the feasibility and safety of left atrial ablations in patients with PLSVC, especially when PLSVC is unknown prior to the ablation procedure. Methods and results: In this retrospective analysis 15 adult patients (mean age 64.6 ± 14.5 years, 53.3% male) with PLSVC undergoing 27 ablation procedures for atrial fibrillation or left atrial flutter were included. In 5 (33.3%) patients PLSVC was only discovered during the procedure. Transseptal puncture (TSP) was declared "difficult" by the ablating physician in 13 of 27 (48.2%) procedures and was not successfully completed in the first attempt in two patients with known PLSVC. Once TSP was successfully completed, all relevant structures were reached both during mapping and ablation in all procedures independent of whether PLSVC was known prior to the procedure. One major complication (3.7%) occurred in 27 procedures in a patient with known PLSVC. In the patients with unknown PLSVC no complication occurred. Conclusion: In experienced hands, left atrial access and ablation in patients with PLSVC is feasible and safe, particularly with regard to patients in whom the PLSVC is unknown prior to the ablation procedure.